Fabrication of Superhydrophobic Surfaces on Aluminum Alloy Via Electrodeposition of Copper Followed by Electrochemical Modification - Huang, Ying; Sarkar, D. K.; Chen, X-Grant (Nano-Micro Letters, 2011)
Superhydrophobic aluminum surfaces have been prepared by means of electrodeposition of copper on aluminum surfaces, followed by electrochemical modification using stearic acid organic molecules. Scanning electron microscopy (SEM) images show that the electrodeposited copper films follow “island growth mode” in the form of microdots and their number densities increase with the rise of the negative deposition potentials. At an electrodeposition potential of −0.2 V the number density of the copper microdots are found to be 4.5×104 cm−2 that are increased to 2.9×105 cm−2 at a potential of −0.8 V. Systematically, the distances between the microdots are found to be reduced from 26.6 μm to 11.03 μm with the increase of negative electrochemical potential from −0.2V to −0.8V. X-ray diffraction (XRD) analyses have confirmed the formation of copper stearate on the stearic acid modified copper films. The roughness of the stearic acid modified electrodeposited copper films is found to increase with the increase in the density of the copper microdots. A critical copper deposition potential of −0.6V in conjunction with the stearic acid modification provides a surface roughness of 6.2 μm with a water contact angle of 157°, resulting in superhydrophobic properties on the aluminum substrates.